Episcopal power and ecclesiastical reform in the German Empire tithes, lordship, and community, 950 - 1150 - Eldevik, John 1973- (Cambridge studies in medieval life and thought, 2012)
Bishops, power and medieval society: a comparative approach -- Social worlds of the ecclesiastical tithe -- Tithes, bishops and society in Frankish Europe -- Landscapes of Episcopal authority:Lucca, Mainz And Salzburg -- Diabolic contracts: the leasing of Pievi and perceptions of order and power in early medieval Italy -- Piety, power and memory: bishops and tithes in the Diocese of Salzburg -- Struggle for tithes in an age of transition